The Effect Of Non-Financial Performance On Managerial Performance Mediated By The Clarity Of Role And Procedural Justice - Erma Setiawati; Andy Dwi Bayu Bawono; Diyah Nurhidayati (Riset Akuntansi dan Keuangan Indonesia, 2021)
The study aims to test the influence of non-financial and managerial performance with variable the clarity of role and procedural justice mediation. This research is a quantitative study using a descriptive approach. The population in this study is a sharia bank employee in Surakarta. The sampling techniques used in this study use convenience sampling. The sample criteria in this study were the respondents who had subordinate employees under it and had worked at least 1 year, as for the samples in this study amounting to 126 respondents. The data used in the study is the primary data collected through surveys in physical form. Data analysis uses multiple linear regression and moderating regression with an absolute value-difference approach. The results of the study with multiple linear regression analyses showed that non-financial performance has an effect on managerial performance, the clarity of the role affecting the managerial performance, procedural justice has an effect on managerial performance, and nonfinancial performance affect the managerial performance with the clarity of role mediation and while the procedural justice variables do not mediate the influence of non-financial performance affecting managerial performance.